2013
DOI: 10.1016/j.ijlp.2013.09.002
|View full text |Cite
|
Sign up to set email alerts
|

The right to life in a suicidal state

Abstract: This paper considers when the State must take positive steps to protect the right to life of a suicidal patient. Using recent developments across the Council of Europe which challenge the traditional 'ugly Samaritan' approach of many common law systems, it contends that whenever and wherever public authorities know or ought to know of a real and immediate risk to the life of an identifiable person, they must take reasonable precautions to minimise it. Even J. S. Mill's approach to liberty, it is suggested, wou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…Management of the advance decision was difficult both emotionally and ethically for some clinicians because it challenged their professional training and their desire to protect vulnerable patients from suicide. The competing pressures of respecting a patient’s right to autonomy while protecting them from the effects of mental disorder found in the current study is a commonly reported dilemma 41. There is evidence from the present study that support for the right to autonomy may be more dominant in clinicians from emergency medicine disciplines, with those from a psychiatric background prioritising prevention of suicide.…”
Section: Discussionmentioning
confidence: 53%
See 2 more Smart Citations
“…Management of the advance decision was difficult both emotionally and ethically for some clinicians because it challenged their professional training and their desire to protect vulnerable patients from suicide. The competing pressures of respecting a patient’s right to autonomy while protecting them from the effects of mental disorder found in the current study is a commonly reported dilemma 41. There is evidence from the present study that support for the right to autonomy may be more dominant in clinicians from emergency medicine disciplines, with those from a psychiatric background prioritising prevention of suicide.…”
Section: Discussionmentioning
confidence: 53%
“…A ‘middle ground’ between these views may help to provide guidance for clinicians. For example, in English law, courts have acknowledged that while some suicidal individuals may have capacity, the overwhelming likelihood is that capacity is impaired to at least some degree 41. Suicidal ideation has been associated with disordered and impulsive decision-making33 34 and evidence indicates that most mental health patients presenting to EDs are judged as not having capacity to make a treatment decision 12.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the risks may be obvious with hindsight, the very "obvious" nature of such risks is an illusion. For example, based on the use a routine risk assessment, 60 per cent of suicides are assessed as low risk and only 3 per cent of those categorised as high risk actually commit suicide (Allen, 2013). Furthermore, even when assessment makes use of formal measures designed to assess suicide risk the situation does not improve.…”
Section: Risk and Rabonementioning
confidence: 99%
“…Two further cases involving the assessment of suicide risk have also had an impact upon risk and its management regarding clinical decision-making. Kingdom (1998) 29 EHRR 245) to protect life could be owed to informal psychiatric patients as well as formally detained patients under the MHA 1983 (Allen 2013) as long as there has been 'an assumption of responsibility by the State for the individual's welfare and safety (including by the exercise of control)' (Rabone v. Pennine Care NHS Foundation Trust, p. 22). The European Court also agreed that the duty could be owed to an informal patient (Reynolds v. United Kingdom (2012) 55 EHRR 35).…”
Section: The Cheshire West Effect (And Other Cases)mentioning
confidence: 99%